PENGARUH PEMBERIAN TERAPI DENGAN TEKNIK MASSAGE TUI NA TERHADAP PENINGKATAN NAFSU MAKAN PADA BALITA - Nursanti, Elpi; Susanti (Universitas Batam, 2025)
A long-lasting decrease in a child's appetite can lead to stunted growth. Handling toddlers with feeding difficulties needs to be considered to maintain health and achieve optimal growth in toddlers. Child growth and development are critical issues that need serious attention. The purpose of this study was to determine the effect of giving TUI NA massage technique therapy on increasing appetite in toddlers. The research method is quantitative, and this type of research is quasi-experimental, where the design form used is one group pre-and post-test design. The population in this study consisted of toddlers in the Tg. Balai Karimun is a total of 48 toddlers. The sample taken was 43 from the population that fit the criteria. Data collection tools or instruments used in this study are questionnaires and SOP Tui Na massage. The result of the t value obtained was -11.165, with a significant value of 0.000. This shows a considerable value smaller than 0.05 (0.000 <0.05), so the hypothesis in this study is accepted. This study concludes that Tui Na massage affects increasing toddler appetite. Keywords : Massage TUI NA, Toddler, Appetite